PENGARUH PENERAPAN APLIKASI E-FAKTUR TERHADAP KEPATUHAN PENGUSAHA KENA PAJAK - Theo Allolayuk (Fakultas Ekonomi dan Bisnis, Universitas Cenderawasih, 2018)
This study aims to see the effect of the application of e-invoices on the compliance of taxable entrepreneurs in Jayapura Primary KPP. The independent variable used is e-invoice tax while the dependent variable is taxable businessman compliance. The population in this study were taxable entrepreneurs who had been confirmed at the KPP Pratama Jayapura, using the convenience sampling method, by distributing questionnaires directly to taxable entrepreneurs who were accidentallyencountered by the researchers. The method of analysis used in this study is simple linear regression with SPSS 16 test tool. The results showed that there was an increase of VAT revenue in KPP PratamaJayapura after the application of tax e-invoice. This is influenced by increased compliance of taxable entrepreneurs after e-invoicing is applied. In this study the application of tax e-invoice has an effect of35.9% on the compliance of taxable entrepreneurs 64.9% influenced by other variables outside the model. Based on the results of the t test, t arithmetic is greater than t table that is 7.165> 1.661 otherwise if it isseen from its significance smaller than 0.05, that is 0,000, it indicates that the e-invoice application partially affects the compliance of taxable entrepreneurs